Hood eaudiobook The legend begins anew. - Lawhead, Stephen R. (King Raven Trilogy., 2006)
For centuries, the legend of Robin Hood and his band of thieves has captivated the imagination. Now the familiar tale takes on new life, fresh meaning, and an unexpected setting. Hunted like an animal by Norman invaders, Bran ap Brychan, heir to the throne Elfael, has abandoned his father's kingdom and fled to the greenwood. There, in the primeval forest of the Welsh borders, danger surrounds him - for this woodland is a living, breathing entity with mysterious powers and secrets, and Bran must find a way to make it his own if he is to survive. Like the forest itself, Hood is deep, dark, and at times savagely brutal - yet full of enchantment and hope. Internationally-acclaimed author Stephen R. Lawhead has created a lyrical rendering of a time-honored story that will lead you down strange pathways into another time and place.